STRATEGI MANAJEMEN KEHUMASAN DALAM MEMBANGUN CITRA POSITIF SEKOLAH DI ERA DIGITAL - Priya Jati, Histura; Sunhaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Advances in information technology have encouraged schools to increasingly maximize the role of public relations management in building a positive image through the use of digital media. This study aims to examine the digital public relations strategies implemented by schools to strengthen their reputations, expand public communication, and increase information reach. Using a qualitative case study approach, this study explores digital public relations practices through interviews, observations, and documentation analysis at schools that actively manage social media and websites as their primary communication channels. The research findings indicate that consistent digital publications, engaging content presentation, and professional social media management can significantly increase school visibility. Furthermore, two-way interaction with the public through comments, private messages, and virtual activities has been shown to strengthen emotional bonds and increase public trust in schools. Digital public relations strategies also contribute to the formation of a positive image through neat visual displays, inspiring narratives, and the rapid and accurate delivery of information. This study confirms that the success of public relations management in the digital era is greatly influenced by the quality of content, the consistency of publications, and the school's ability to utilize communication technology. The research results provide theoretical contributions to the development of educational public relations studies and offer practical recommendations for schools to improve the quality of digital communication. Thus, digital public relations strategies are a crucial effort in building a sustainable positive school image amidst the increasingly rapid development of information technology.